GIANT HYPOGASTRIC ARTERY ANEURYSM AFTER PREVIOUS ABDOMINAL AORTIC ANEURYSM EXCLUSION, WITH A HOSTILE ABDOMEN AND ANATOMY - Luís Machado; Armando Mansilha (Angiologia e Cirurgia Vascular, 2018)
The widespread use of various imaging modalities, allow that hypogastric aneurysms have been increasingly detected. Usually asymptomatic, but once clinical symptoms occur, it must be supposed immediately that the hypogastric aneurysms have ruptured or that is compressing neighboring abdominal structures. We describe a patient with a giant hypogastric aneurysm, after a AAA repair, compressing the ureter and spinal roots, treated by open surgery.